The type and timing of patent ductus arteriosus treatment was associated with neurodevelopment when extremely preterm infants reached 6.5 years. (15th July 2020) - Gudmundsdottir, Anna; Broström, Lina; Skiöld, Beatrice; Källén, Karin; Serenius, Fredrik; Norman, Mikael; Aden, Ulrika; Bonamy, Anna‐Karin Edstedt
Abstract: Aim: This study investigated patent ductus arteriosus (PDA) treatment and neurodevelopmental outcomes when extremely preterm born children reached 6.5 years. Method: Our cohort was 435 children with neonatal PDA treatment data and neurodevelopmental follow‐up data, born in 2004‐2007, who participated in the Extremely Preterm Infants in Sweden Study. Pharmacological or surgical PDA treatment and the age at PDA treatment, were investigated in relation to the risks of moderate to severe neurodevelopmental impairment (NDI) and full‐scale intelligence quotient (FSIQ) at 6.5 years. Results: The children who received PDA drug treatment, including those who also had surgery, had the same risk of moderate to severe NDI or lower FSIQ as untreated children. However, children who had primary PDA surgery faced increased risks of NDI, with an adjusted incidence rate ratio of 1.62 (95% confidence interval [CI] 1.28‐2.06) and a lower adjusted mean difference FSIQ of −7.1 (95% CI −11 to −3.2). Surgery at less than 10 days of life was associated with a significantly increased risk of moderate to severe NDI and lower FSIQ than surgery after 20 days. Conclusion: Drug treatment followed by deferred surgery appeared to be a safer option for extremely preterm infants severely affected by PDA.